2010
DOI: 10.1021/ef9008955
|View full text |Cite
|
Sign up to set email alerts
|

Constant-Pressure Technique for Gas Diffusivity and Solubility Measurements in Heavy Oil and Bitumen

Abstract: A modified pressure decay method has been designed and tested for more reliable measurements of molecular diffusion coefficients of gases into liquids. Unlike the conventional pressure decay method, the experimental setup has been designed such that the interface pressure and consequently the dissolved gas concentration at the interface are kept constant. This is accomplished by continuously injecting the required amount of gas into the gas cap from a secondary supply cell to maintain the pressure constant at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 18 publications
1
83
0
Order By: Relevance
“…Other researchers have proposed and developed different mathematical solutions by modeling the interface boundary condition differently. With dependence on how the interface boundary condition is defined, a range of simple to very complex solutions can be expected for this problem Mehrotra 2000, 2002;Civan and Rasmussen 2006;Rasmussen and Civan 2009;Tharanivasan et al 2004;Etminan et al 2010). It is evident that there is not a considerable error in using simple method for determination of diffusion coefficient.…”
Section: Determination Of Diffusion Coefficient From Pressure Datamentioning
confidence: 99%
“…Other researchers have proposed and developed different mathematical solutions by modeling the interface boundary condition differently. With dependence on how the interface boundary condition is defined, a range of simple to very complex solutions can be expected for this problem Mehrotra 2000, 2002;Civan and Rasmussen 2006;Rasmussen and Civan 2009;Tharanivasan et al 2004;Etminan et al 2010). It is evident that there is not a considerable error in using simple method for determination of diffusion coefficient.…”
Section: Determination Of Diffusion Coefficient From Pressure Datamentioning
confidence: 99%
“…The step changes in the pressure within the PVT cell in combination with a developed mathematical model were used to predict the diffusion coefficients. Later, Jamialahmadi et al (2006) and Etminan et al (2010) reported a new method for predicting diffusion coefficients of gases in heavy oil from experimental volume-time profiles. In this method, the volume changes of the PVT cell were recorded and used to calculate diffusion coefficients of gases in liquid hydrocarbon systems instead of the pressure changes.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies neglected interface mass transfer resistance and limited this parameter to the situations of very high mass transfer rates which are not encountered in many practical cases [5]. These research works, assumed an equilibrium boundary condition at the gas-liquid interface [6][7][8]; however, some studies put forward the theory of existence of the resistance at interface as a non-equilibrium boundary condition, and this new boundary condition was solved analytically in the form of an infinite Fourier series [9,10]. Employing such boundary condition will be important when a high pressure gas suddenly contacts with a liquid in which gas does not have enough time to reach equilibrium [11].…”
Section: List Of Symbolsmentioning
confidence: 99%